A climosequence of chronosequences in southwestern Australia. (18th January 2018) - Turner, B. L.; Hayes, P. E.; Laliberté, E.
Summary: To examine how climate affects soil development and nutrient availability over long timescales, we studied a series of four long‐term chronosequences along a climate gradient in southwestern Australia. Annual rainfall ranged from 533 to 1185 mm (water balance from −900 to +52 mm) and each chronosequence included Holocene (≤ 6.5 ka), Middle Pleistocene (120–500 ka) and Early Pleistocene (∼2000 ka) dunes. Vegetation changed markedly along the climosequence, from shrubland at the driest site to Eucalyptus forest at the wettest. Soil pH was similar in the youngest soil of each chronosequence, although the carbonate and P contents of the parent sand declined from dry to wet along the climosequence, presumably linked to variation in offshore productivity. Despite this, soil development and associated nutrient status followed remarkably consistent patterns along the four chronosequences. Pedogenesis involved decalcification and secondary carbonate precipitation in Holocene soils and leaching of iron oxides from Middle Pleistocene soils, leading ultimately to bleached quartz sands in the oldest soils. Along all chronosequences soil pH and total P declined, whereas C:P and N:P ratios increased, which is consistent with the predicted change from N to P limitation of vegetation during ecosystem development. The expected unimodal pattern of leaf area index was most pronounced along wetter chronosequences, suggesting an effect of climate on the expression of retrogression. The four chronosequences do not appear to span a pedogenic climate threshold, defined as an abrupt change in soil properties across a relatively small change in climate, because exchangeable phosphate and base cations declined consistently during long‐term pedogenesis. However, the proportion of total P in organic form was greater along wetter chronosequences. We conclude that soil and nutrient availability on the coastal sand plains of southwestern Australia change consistently during long‐term pedogenesis, despite marked variation in modern vegetation and climate. The four chronosequences provide a rare soil‐age × climate framework within which to study long‐term ecosystem development. Highlights: We describe four long‐term coastal dune chronosequences spanning a climate gradient in a global biodiversity hotspot. Pedogenesis involves depletion of phosphorus and cations linked to decalcification and subsequent podsolization. Climate has relatively little effect on patterns of nutrient availability during ecosystem development along the climosequence. The age by climate framework enables study of effect of edaphic change on above‐ and below‐ground communities.